Getting the news in milliseconds: The role of early novelty detection in active electrosensory exploration - Angel A. Caputi; Alejo Rodríguez-Cattáneo; Joseph C. Waddell; Ana Carolina Pereira; Pedro A. Aguilera (BioSystems, 2023)

A simple model of the electrosensory electromotor loop in Gymnotus omarorum - Angel A. Caputi; Joseph C. Waddell; Pedro A. Aguilera (BioSystems, 2023)

Waveform discrimination in a pair of pulse‐generating electric fishes - Joseph C. Waddell; Angel A. Caputi (Journal of Fish Biology, 2020)
Studies of pulse‐type gymnotiform electric fishes have suggested that electric organ discharge waveforms (EODw) allow individuals to discriminate between conspecific and allospecific signals, but few have approached this experimentally. Here we implement a phase‐locked playback technique for a syntopic species pair, Brachyhypopomus gauderio and Gymnotus omarorum . Both species respond to changes in stimulus waveform with a transitory reduction in the interpulse interval of their self‐generated discharge, providing strong evidence of discrimination. We also document sustained rate changes in response to different EODws, which may suggest recognition of natural waveforms.

Imaging in electrosensory systems - Ana Carolina Pereira; Angel Ariel Caputi (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Electric imaging through active electrolocation: implication for the analysis of complex scenes - Jacob Engelmann; João Bacelo; Michael Metzen; Roland Pusch; Beatrice Bouton; Adriana Migliaro; Angel Caputi; Ruben Budelli; Kirsty Grant; Gerhard von der Emde (Biological Cybernetics, 2008)